Nutritional epidemiological profile of the population assisted in a cancer prevention campaign - Cristina Mendes Gusmão, Amanda; Donato Bauman, Claudiana; Teles Guerra, Lucas; de Pinho, Lucineia; Antunes Uramoto, Marilena; Fagundes Silveira, Marise; Bernardina Miranda Soares, Príscila (Revista Unimontes Científica, 2020)
PERFIL EPIDEMIOLÓGICO NUTRICIONAL DA POPULAÇÃO ASSISTIDA EM CAMPANHA DE PREVENÇÃO DO CÂNCER Abstract: Goal: To describe the epidemiological and nutritional profile and lifestyle habits of the population assisted in the 8th Task Force for the cancer prevention in the year 2018, held in the city of Montes Claros, MG. Method: It is a descriptive epidemiological study, with data obtained in visits in the nutrition stand in the 8th Task Force to prevent cancer. A structured questionnaire was used covering sociodemographic characteristics, life habits, cancer family history and food consumption. The nutritional status was evaluated according to the body mass index. The data were tabulated and analyzed by means of descriptive statistics. Results: 321 individuals participated, being 81.9% females and with a mean age of 52.45 (±14.06) years. Among the participants, 47.2% reported cancer family history. The practice of physical activity three times a week was reported by 29.0%. The prevalence of excess weight was 66.8%. The daily food consumption of fruits and vegetables was 34.1% and 50.9%, respectively. Conclusion: The nutritional approach and suitability of the life habits must be actions incorporated for the cancer prevention. Resumo: Objetivo: Descrever o perfil epidemiológico nutricional e hábitos de vida da população assistida no 8º Mutirão de prevenção ao do câncer no ano de 2018, realizado na cidade de Montes Claros, MG. Método: Trata-se de um estudo epidemiológico e descritivo, mediante dados obtidos em atendimentos na tenda da nutrição no 8º Mutirão de Prevenção ao Câncer. Utilizou-se um questionário estruturado abrangendo características sociodemográficas, hábitos de vida, histórico familiar de câncer e consumo alimentar. Avaliou-se o estado nutricional segundo o índice de massa corporal. Os dados foram tabulados e analisados por meio de estatística descritiva. Resultados: Participaram 321 indivíduos, sendo 81,9% do sexo feminino e com média de idade de 52,45 (±14,06) anos. Entre os participantes 47,2% relataram história familiar de câncer. A prática de atividade física em três vezes na semana foi relatada por 29,0%. A prevalência de excesso de peso foi de 66,8%. O consumo alimentar diário de frutas e verduras foi de 34,1% e 50,9%, respectivamente. Conclusão: A abordagem nutricional e adequação dos hábitos de vida devem ser ações incorporadas para a prevenção do câncer.